2010
DOI: 10.1016/j.bmcl.2009.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Polar 3-alkylidene-5-pivaloyloxymethyl-5′-hydroxymethyl-γ-lactones as protein kinase C ligands and antitumor agents

Abstract: A series of DAG-lactones with polar 3-alkylidene substituents have been investigated as PKC-α ligands and antitumor agents. Extensive analysis of structure activity relationships for the 3-alkylidene chain revealed that polar groups such as ether, hydroxyl, aldehyde, ester, acyloxy, and amido were tolerated with similar binding affinities and reduced lipophilicities compared to the corresponding unsubstituted alkylidene chain. Among the derivatives, compounds 5, 6 and 8 with an ether type of side chain showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In addition, the Eheteroarylidenes showed better binding affinities to PKCα and RasGRP3 compared with the respective Z-isomers. DAG-lactones with polar groups in the 3-alkylidene chains were synthesized to improve water solubility [179]. In most cases, the modifications had little effect on binding affinity, and ligands with good PKCα-binding affinity (Ki = 3.2-5 nM) also showed significant antitumor activity against colon cancer and leukemia cell lines.…”
Section: Selectivity Of Dag-lactones Among C1 Domain Containing Proteinsmentioning
confidence: 99%
“…In addition, the Eheteroarylidenes showed better binding affinities to PKCα and RasGRP3 compared with the respective Z-isomers. DAG-lactones with polar groups in the 3-alkylidene chains were synthesized to improve water solubility [179]. In most cases, the modifications had little effect on binding affinity, and ligands with good PKCα-binding affinity (Ki = 3.2-5 nM) also showed significant antitumor activity against colon cancer and leukemia cell lines.…”
Section: Selectivity Of Dag-lactones Among C1 Domain Containing Proteinsmentioning
confidence: 99%
“…Kang et al synthesized and investigated a series of DAG-lactones with polar 3-alkylidene substituents as PKC α and antitumor agents ( Figure 17 ). The structure-activity relationships revealed that compounds 312 , 313 , and 314 with an ether side chain have high binding affinities (K i = 3–5 nM) and excellent antitumor effects on colon cancer (Colo205, GI 50 = 0.120–0.260 μg/mL) and leukemia cancer (K562, GI 50 = 0.140–0.200 μg/mL) cell lines [ 195 ].…”
Section: Biological Activities and Chemistry Of Natural And Synthementioning
confidence: 99%
“…Due to high lipophilicity of synthesized DAGLs, it was attempted to reduce the lipophilicity by incorporating more polar side substituents in the 3-alkylidene chain. DAG-lactones with polar 3-alkylidene chains were synthesized by alkylation of the protected 5,5-disubstituted γ -lactone with various polar side chains ( Scheme 69 ) [ 195 ].…”
Section: Biological Activities and Chemistry Of Natural And Synthementioning
confidence: 99%
See 1 more Smart Citation